182 CD30 and Epstein-Barr Virus-Positive Diffuse Large B-Cell Lymphoma With Aberrant T-Cell Marker Expression Arising in Low-Grade Follicular Lymphoma: A Case Report. (11th January 2018) - Mann, Steven; Zhang, Shanxiang
Abstract: Aberrant expression of T-cell markers such as CD3 is exceedingly rare in B-cell neoplasms, with CD2 and CD7 being the most commonly reported. Failure to recognize this occurrence may lead to diagnostic challenges. We present a CD30, Epstein-Barr virus-positive diffuse large B-cell lymphoma in association with low-grade follicular lymphoma, with aberrant expression of pan-T-cell markers in the diffuse large B-cell lymphoma. The patient was an 81-year-old man with a history of multiple medical comorbidities who presented with recurrent squamous cell carcinoma of the left ear. Three months after completing adjuvant radiation therapy, the tumor was resected along with bilateral cervical lymph nodes. Histologically, all 19 lymph nodes showed architectural effacement by nodules of predominantly small atypical lymphocytes. Seven lymph nodes also showed foci of diffuse areas with large mononucleated and multinucleated atypical cells. The small atypical lymphocytes were positive for CD20, PAX5, CD79a, OCT.2, CD10, BCL-2, and BCL-6, and negative for T-cell markers. The large atypical cells in the diffuse areas were positive for CD30, CD2, CD3, CD5, CD7, MUM-1, partially positive for CD4 and CD8 in addition to CD20, PAX5, CD79a, and OCT.2. Epstein-Barr virus was positive in the diffuse large B-cell lymphoma but not follicular lymphoma by in situ hybridization for Epstein-Barr virus-encoded RNAs. Both the large and small atypical lymphocytes were negative for CD15, TCR gamma, TCR beta, TIA1, granzyme B, and perforin. Polymerase chain reaction revealed a clonal immunoglobulin heavy chain gene rearrangement and polyclonal T-cell receptor gamma gene rearrangement. Further positron emission tomography study revealed left neck and abdominal involvement. A biopsy of the retroperitoneal mass showed low-grade follicular lymphoma. The patient was treated with rituximab; however, he worsened clinically. At last discharge, he suffered from recurrent pleural effusions and a new lung mass suspicious for metastatic squamous cell carcinoma.